Valoración técnica de cocinas solares tipo caja con reflectores interiores de tres, cinco y diez pasos. - Cuenca Jiménez, Henry Augusto (2014)
This research was framed in the study of box type solar cookers with internal reflectors of three, five and ten steps in order to evaluate them and determine the most efficient construction. First a bibliographic compilation of the main features of existing prototypes were made. Simulation was then performed in Matlab Simulink software and the results were determined to solar cooker 3 most efficient. He then designed and built the solar cooker solar cooking 3 and 10 are solar cookers finally 3 and 10 was monitored based on the ASAE S580 standard and its efficiency was determined, solar cook 3 had 14,1 % with 1,5 liters of water and solar cook 10 was 7,3 % with 7 liters of water in the city of Loja. With the prototype Solar Cook 3 greater use of solar radiation was achieved and a maximum temperature of 95 °C, enough to heat, pasteurized, boil and cook.